Organofacies composition of Upper Jurassic – lowermost Cretaceous source rocks, Danish Central Graben, and insight into the correlation to oils in the Valdemar Field. (April 2020) - Ponsaing, L.; Mathiesen, A.; Petersen, H.I.; Bojesen-Koefoed, J.A.; Schovsbo, N.H.; Nytoft, H.P.; Stemmerik, L.
Abstract: The organic-rich marine shales of the Upper Jurassic - lowermost Cretaceous Farsund Formation are the main hydrocarbon source rocks for the Cretaceous chalk reservoir of the Valdemar Field (Danish North Sea). Geochemical analyses of oil extracts from core samples across the greater Valdemar Field show substantial heterogeneity of the reservoir oils, suggesting contribution from kitchen areas with source rocks of variable organofacies and thermal maturity. In order to better understand the source rock facies that charged the field, a refined organofacies characterization of the Upper Jurassic - lowermost Cretaceous marine shale source rock succession (Farsund Formation) in the Danish Central Graben was established. This organofacies characterization is based on integration of petrographic and geochemical data and demonstrates large variations in both the regional and local distribution of the organofacies at the sequence level in the shales within the Danish Central Graben. In addition, the organofacies characterization shows that the respective sequences in the succession may be represented by several organofacies at the same time. Part of the explanation to the heterogeneity in the oil types accumulated within the Valdemar Field may lie in the presence of different organofacies within the uppermost sequences (Vol-3 to Ryaz-1) in the three kitchen areas. Each organofacies presumable generates different types of oils and the variation in the relative proportions of the different organofacies likely determines the composition of the generated oils. One dimensional (1-D) maturity modelling at three pseudo-well locations, each representing a potential Farsund Formation kitchen, shows that all kitchens are in the main oil window and that mainly oil was expelled from the Volg-3 to Ryaz-1 sequences. Modelling indicates that (i) average values of TOC, HI, thickness and the kinetic model are the main controls on generation and expulsion of hydrocarbons; and (ii) by increasing these parameters, expulsion could also occur from the lower part of the succession. Highlights: Six new types of organofacies for the Farsund Formation have been defined. The regional and local distribution of the organofacies varies at sequence level. The stratigraphic and lateral variations in organic facies are illustrated. The organofacies may be different in other areas due to the large local differences. Several organofacies may be present at the same time within the respective sequences.